EXPOSURE TO E-CIGARETTE ADVERTISEMENT AMONG FIRST-YEAR STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2024 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the prevalence of exposure to e-cigarette advertising and identify associated factors among first-year students at Hanoi Medical University in 2024.Methods: A cross-sectional descriptive study was conducted among 457 first-year medical students from 11/2023 to 6/2024.Results: The study indicated that two-thirds of first-year students (67.0%) reported exposure to e-cigarette advertising, with social media being the primary channel. Students who had acquaintances using e-cigarettes were more likely to be exposed to e-cigarette advertising compared with those who did not (OR = 1.6; 95% CI: 1.1–2.4; p = 0.026). In addition, students who were exposed to e-cigarette smoke in the past 30 days were also more likely to encounter e-cigarette advertising than those who were not exposed (OR = 1.9; 95% CI: 1.2–2.9; p = 0.04).Conclusions: A high prevalence of exposure to e-cigarette advertising was observed among first-year students at Hanoi Medical University, with social media being the most common source of exposure. A statistically significant association was found between exposure to e-cigarette advertising and both having acquaintances who use e-cigarettes and passive exposure to e-cigarette smoke in the past 30 days.
Keywords: Advertising exposure, advertising, e-cigarette, university student.